Midgut volvulus and complex meconium peritonitis in a fetus with undiagnosed cystic fibrosis - Kaeli J. Yamashiro; Laura A. Galganski; Shinjiro Hirose; Rebecca A. Stark (Elsevier, 2019)
In utero small bowel volvulus with meconium peritonitis is a rare complication of cystic fibrosis.We report the case of fetal small bowel volvulus with necrosis, perforation and meconium peritonitis in a fetus with undiagnosed cystic fibrosis. The mother presented with four days of decreased fetal movement and ultrasound findings of fetal small bowel dilation with wall thinning and ascites. The fetus' status declined three days thereafter, prompting an emergent delivery. The infant was born with peritonitis and underwent an exploratory laparotomy with a small bowel resection and interval anastomosis. Following restoration of continuity, the patient was able to tolerate oral and enteral nutrition with appropriate growth. This report provides an example of the signs, symptoms and sonographic findings associated with this rare fetal complication and explores the intricacies of prenatal genetic testing. Keywords: Cystic fibrosis, Fetal cystic fibrosis complication, Fetal small bowel volvulus, Fetal small bowel perforation, Complicated meconium peritonitis